The Impact of Mining on Spatial Inequality Recent Evidence from Africa - Addison, Tony; Boly, Amadou; Mveyange, Anthony (World Bank, Washington, DC, 2017)
This paper investigates the relationship between mining and spatial inequality in Africa during 2001-12. The identification strategy is based on a unilateral causation between mining and district inequality. The findings show that when minerals are aggregated, mining increases district inequality. But an analysis of individual minerals shows that mining affects district inequality positively and negatively, suggesting that mineral wealth can be a curse and a blessing. Further analysis suggests that these results largely depend on whether mining is active or closed, the scale of mining operations, the value of minerals extracted, and the nature of mining activities -- important dimensions for shaping mining policies aimed at bolstering socioeconomic development in Africa.